Histone H3.3 phosphorylation promotes heterochromatin formation by inhibiting H3K9/K36 histone demethylase. Issue 8 (22nd April 2022) - Udugama, Maheshi; Vinod, Benjamin; Chan, F Lyn; Hii, Linda; Garvie, Andrew; Collas, Philippe; Kalitsis, Paul; Steer, David; Das, Partha P; Tripathi, Pratibha; Mann, Jeffrey R; Voon, Hsiao P J; et al.
Abstract: Histone H3.3 is an H3 variant which differs from the canonical H3.1/2 at four residues, including a serine residue at position 31 which is evolutionarily conserved. The H3.3 S31 residue is phosphorylated (H3.3 S31Ph) at heterochromatin regions including telomeres and pericentric repeats. However, the role of H3.3 S31Ph in these regions remains unknown. In this study, we find that H3.3 S31Ph regulates heterochromatin accessibility at telomeres during replication through regulation of H3K9/K36 histone demethylase KDM4B. In mouse embryonic stem (ES) cells, substitution of S31 with an alanine residue (H3.3 A31 –phosphorylation null mutant) results in increased KDM4B activity that removes H3K9me3 from telomeres. In contrast, substitution with a glutamic acid (H3.3 E31, mimics S31 phosphorylation) inhibits KDM4B, leading to increased H3K9me3 and DNA damage at telomeres. H3.3 E31 expression also increases damage at other heterochromatin regions including the pericentric heterochromatin and Y chromosome-specific satellite DNA repeats. We propose that H3.3 S31Ph regulation of KDM4B is required to control heterochromatin accessibility of repetitive DNA and preserve chromatin integrity.